HYDROXYAPATITE-SUPPORTED TRI-METALLIC CATALYST FOR HYDROGEN PRODUCTION FROM STEAM REFORMING OF GLYCEROL (Jurnal Teknologi (Sciences & Engineering), 2016)
Glycerol is a byproduct of biodiesel industry that has high economic value to produce hydrogen as an energy source. The selection of catalyst support for active metal catalyst in hydrogen production is a major concern since it affects the activity of metal catalyst during the steam reforming process of glycerol. Besides that, bio-based material as catalyst support provides attractive choice as it is more environmentally friendly. In this study, hydroxyapatite (HAP) as support material for tri-metallic catalyst Ni-Ce-Cu was prepared using deposition-precipitation method and used in steam reforming reaction of glycerol to produce hydrogen. The catalyst prepared was characterized by BET, FE-SEM, EDX, and TEM. The catalytic activity tests were conducted at atmospheric pressure and temperatures between 400 – 600 oC in a tubular micro-reactor. Glycerol-water ratios used were 1:4, 1:8, and 1:16. It was found that the highest hydrogen yield (55.0%) was obtained at temperature of 600 oC and glycerol-water ratio of 1: 8 with glycerol conversion of 94.0%.